The Value of Intellectual Property Rights to Firms. - Greenhalgh, C; Rogers, M (Department of Economics (University of Oxford), 2007)
Economists view intellectual property rights (IPRs) as policy tools for encouraging innovation. There are many types of IPRs and of institutions concerned with their administration. We begin by outlining how these complex and varied rights are supposed to work and how they interact with other characteristics of firms and markets. We then survey the available literature on patents, trade marks and copyright to assess the value of these IPRs to firms and the costs to firms of acquiring and defending their rights. The paper concludes with suggestions for topics requiring further research to better inform public policy in this field.